Inhibition of calpain9 attenuates peritoneal dialysis-related peritoneal fibrosis - Li, Fang; Wang, Yu; Tian, Jianwei; Zhou, Zhanmei; Yin, Wei; Qin, Xianhui; Wang, Huizhen; Zeng, Tao; Li, Aiqing; Jiang, Jianping (Frontiers in Pharmacology, 2022)
Abstract Aim. Peritoneal dialysis is a common renal replacement method for end-stage renal disease. Long-term peritoneal dialysis leads to peritoneal dialysis-related peritoneal fibrosis, which leads to a cessation of treatment. Calpain is a protein belonging to calcium-dependent endopeptidase family and plays an important role in extracellular matrix remodeling. Here, we evaluated the effect of calpain in peritoneal dialysis-related peritoneal fibrosis. Methods. We established two animal models of peritoneal fibrosis and inhibited the activity of Calpain, and then collected peritoneal tissue to evaluate the progress of fibrosis and the changes of Calpain and β-catenin. We obtained Rat peritoneal mesothelial cells and Human peritoneal mesothelial cell line and stimulated with TGF-β to produce extracellular matrix. Next we inhibited Calpain activity or reduced Calpain9 expression, and then assessed changes in extracellular matrix and β-catenin. Results. Inhibition of calpain activity attenuated chlorhexidine glucose and peritoneal dialysis-induced peritoneal thickening and β-catenin expression in mice. In addition, compared with the control group, when primary rat peritoneal mesothelial cells or human peritoneal mesothelial cells were treated with transforming growth factor beta, down-regulation of calpain activity inhibited the expression of Fibronectin and Collagen I, and increased the expression of E-cadherin. These changes could be adjusted after silencing calpain9. Finally, calpain9 deficiency was associated with down-regulation of Fibronectin and β-catenin in human peritoneal mesothelial cells. Conclusions. Our results suggest that calpain9 may be a key molecule in mediating peritoneal dialysis-related peritoneal fibrosis.